2009
DOI: 10.1007/s11071-009-9482-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear resonances and self-excited oscillations of a rotor caused by radial clearance and collision

Abstract: This paper investigates oscillations in a flexible rotor system with radial clearance between an outer ring of the bearing and a casing by experiments and numerical simulations. The mathematical model considers the collisions of the bearing with the casing. The following phenomena are found: (1) Nonlinear resonances of subharmonic, super-subharmonic and combination oscillation occur. (2) Self-excited oscillation of a forward whirling mode occurs in a wide range above the major critical speed. (3) Entrainment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The motivation for this research work comes from current interest in developing mathematical and computational tools for the dynamics of multibody systems in which the effects of clearance, surface compliance, friction and lubrication in real joints are taken into account [1][2][3][4][5][6]. These phenomena can be included in a multibody system with a spherical joint, and in many applications the function of the mechanical systems strongly depends on them.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for this research work comes from current interest in developing mathematical and computational tools for the dynamics of multibody systems in which the effects of clearance, surface compliance, friction and lubrication in real joints are taken into account [1][2][3][4][5][6]. These phenomena can be included in a multibody system with a spherical joint, and in many applications the function of the mechanical systems strongly depends on them.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out about the impact of the clearance on the contact stresses [8] and also their impact on the rotor-stator collisions and related resonances and self-excited vibrations [9]. Interestingly, influence of joint clearances were also studied [10].…”
Section: Bearing Systemmentioning
confidence: 99%
“…Ishida et al (83) reported that self-excited oscillations occur in addition to various nonlinear resonance in a system with radial clearance between a bearing holder and a housing. Figure 16 shows the experimental setup and response curves.…”
Section: Self-excited Oscillation Due To Clearancementioning
confidence: 99%